CONTRADICTIONS IN REGIONAL DEVELOPMENT ASSESSMENT: IN WHAT MEAN WE COULD SPEAK ABOUT ECONOMIC CONVERGENCE IN EUROPEAN UNION? - Janno Reiljan (European Regional Science Association (ERSA), 2010)
The objective of current article is to assess EU regional economic development imbalance and its change, by implementing an indicator system of regional development disparities. The quantitative measurement problems of regional development imbalance have not received sufficient attention. Barro and Sala-i-Martin (1991, 1995) have shown the properties of two complicated indicators of regional development imbalance dynamics - β-convergence and δ-convergence that are most widely used in empirical analyses. The EU official statistical assessment of regional economic development imbalance refers to the dispersion of regional GDP per inhabitant. This approach is based on a different methodology. We determined a number of additional regional development imbalance indicators and tackeld the following research tasks: * analysis of general basics and formation of comprerensive indicator system for assessment of regional disparities and its trends in economic development; * empirical analysis of imbalance and its dynamics between economic development of EU member countries on the base of the comprehensive indicator system using GDP in market prices and PPP (Purchasing Power Parity) prices; * eliminating of the price change impact from assessments of regional economic development imbalance dynamics. Our results explain the absolute and relative regional development imbalance and its dynamics in 1996-2008 in EU as a whole and in "old" and "new" member state groups. Regional development imbalances point to improvement necessities of quantitative measurement of regional economic development imbalance and its dynamics.
Keywords: 330; regional economic development; empirical assessment methods; European Union